EL RESURGIMIENTO DE LA POLÍTICA INTERESTATAL EN UNA ÉPOCA DE TRANSNACIONALIZACIÓN - Alfredo Miranda, Roberto (2023)
Since the seventies, the transnational processes have outlined new challenges for both world policy and economy. Many of the sceneries that appear break the traditional parameters international relations move in. An example of this is the feature that builds up intercultural relations and the impact they pose among the statal actors. However, the complications that transnational processes frequently exert in the interstatal relations, cannot alter these relations as it is usually supposed. On the contrary, as the transnational processes require interstatal policy, it is not by chance the resurgence of this policy .